UPAYA MENINGKATKAN HASIL BELAJAR BIOLOGI DENGAN METODE TPS DISERTAI EKSPERIMEN PADA SISWA SMAN 1 BATANGHARI LAMPUNG TIMUR - Chisca Mutiara (Bioedukasi Jurnal Pendidikan Biologi, 2011)
The purpose of the research is to increasing students learning outcomes. This method provides a direct experience for students, students' thinking skills, develop collaborative attitude with his partner and share knowledge with other students. The subjects in this research were students on grade X3 of SMAN 1 Batanghari academic year 2009/2010. This research was conducted on November 2009 which was carried out in 2 cycles. Each cycle is held 3 times meetings and every meeting in each cycle carried out the evaluation.The results of this research show that the students learning outcomes in the first cycle with learning completeness percentage 53.13% with an average rating of 67.65, on the second cycle increases with the percentage of mastery learning to be 84.37% with an average rating of 83.28. Based on the results and discussion can be concluded that learning with TPS that accompanied with experiments can increasing students learning outcomes. The researchers suggest to teachers can be implement the TPS method accompanied with experiments to increasing student learning outcomes. Kata Kunci : TPS, eksperimen, hasil belajar